Optimized segmented heat source for the numerical simulation of welding-induced deformation in large structures. (March 2018) - Wang, Haichao; Wang, Zhijiang; Bai, Pengfei; Hu, Shengsun; Zhang, Yanshen; Wang, Ren
Highlights: A feasible and highly efficient optimized segmented heat source was proposed. The numerical model showed acceptable accuracy with a higher efficiency. Optimized segmented heat source is applicable to welding with different travel speeds. Abstract: A segmented heat source is typically used in welding processes with high energy density and high welding speed, such as laser beam welding. In such welding processes, the intense heat source runs through one segment so quickly that the heating processes in each segment could be considered as a segmented heat source with the largest heat flux heating in a short time. It is then possible to use a segmented heat source model to reduce the computation time. In the present work, a feasible and highly efficient optimized segmented heat source, in which cooling time is considered, was proposed to extend its application area. The optimized segmented heat source could be applied to simulate welding processes with various welding speeds and to simulate large structures with high efficiency. The axial strain in welding a pipe with external diameter of 510 mm and wall thickness of 13.5 mm by shielded metal arc welding was measured to verify the accuracy of the proposed heat source. The temperature filed characteristics and the prediction of welding deformation and its distribution were discussed to measure the accuracy and efficiency of the model with the proposed heat source. The model with the optimized segmented heat source predicts the welding deformation with higher accuracy compared to the model with the traditional segmented heat source; however, the efficiency was compromised. Its accuracy is in the range of 10% compared to the model with a double-ellipsoidal heat source, but it is more effective.